2002
DOI: 10.1006/jsvi.2001.4039
|View full text |Cite
|
Sign up to set email alerts
|

Linear Elastic Response of Tubes to Internal Detonation Loading

Abstract: This paper deals with the structural response of a tube to an internal gaseous detonation. An internal detonation produces a pressure load that propagates down the tube. Because the speed of the gaseous detonation can be comparable to the flexural wave group speed, excitation of flexural waves in the tube wall must be considered. Flexural waves can result in much higher strains and stresses than static loading with the same loading pressures. Experiments and numerical simulations were used to determine the str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 17 publications
1
95
0
Order By: Relevance
“…The behavior of tubes near this critical velocity has been studied by numerous authors [4,11,12,20] who have found that a resonance between the traveling load and the speed of flexural waves results in highly amplified displacements, stresses, and strains. This critical velocity is the minimum phase speed of sinusoidal waves in the tube, and hence is located at the minimum of the lowest branch of the dispersion curve (see Fig.…”
Section: Comparison Of Transient Shell Model With Femmentioning
confidence: 99%
See 3 more Smart Citations
“…The behavior of tubes near this critical velocity has been studied by numerous authors [4,11,12,20] who have found that a resonance between the traveling load and the speed of flexural waves results in highly amplified displacements, stresses, and strains. This critical velocity is the minimum phase speed of sinusoidal waves in the tube, and hence is located at the minimum of the lowest branch of the dispersion curve (see Fig.…”
Section: Comparison Of Transient Shell Model With Femmentioning
confidence: 99%
“…This deformation is zero at the ends of the tube and reaches a maximum radial displacement of δ at the center. Deformation of this form is motivated by the sinusoidal vibrations that are observed behind a shock or detonation wave [4], which will be considered in more detail in Sec. 5.…”
Section: Errors Due To Strain-displacement Rela-tionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideal detonations propagate at approximately the Chapman-Jouguet (CJ) detonation speed and the detonation pressure axisymmetrically loads the pipe. The structural response of a straight pipe to a detonation propagating at a constant speed was studied in depth by Beltman [5], but industrial piping systems are more complex.…”
Section: Introductionmentioning
confidence: 99%